"Any time because I am ready": willingness to use long-acting injectable HIV PrEP among female barmaids in Dar es Salaam, Tanzania - Akyoo, Winfrida; Mosha, Idda Hubert; Jahn, Albrecht; Mpembeni, Rose (Frontiers in Public Health, 2025)
BackgroundHuman immunodeficiency virus (HIV) is still a major global public health problem. Sub-Saharan Africa remains the most severely affected, accounting for 69% of the people living with HIV worldwide. Currently, Pre-Exposure Prophylaxis [PrEP] pills are offered but are highly affected by non-adherence. Long-acting injectable PrEP has the potential to improve adherence.ObjectiveThis study aimed to explore awareness and willingness to use long-acting injectable HIV pre-exposure prophylaxis among users and non-PrEP user female barmaids in Ubungo municipality in Dar es Salaam, Tanzania.MethodsThis phenomenological study used in-depth interviews to collect data. A total of 17 study participants were purposively selected. Audio-recorded interviews were transcribed verbatim and translated into English. A thematic approach was used to identify patterns in the data. Key themes were coded using NVivo14 and then summarized into key findings.FindingsThe findings revealed that participants who were PrEP pill users and non-users were aware of PrEP pills. Few of the PrEP pill users were aware of the long-acting injectable PrEP. The majority of both users and non-users of PrEP pills were willing to use the long-acting injectable PrEP. A few PrEP non-users expressed fear for PrEP, citing safety, and insisted on continuous condom use.ConclusionThe majority of participants are aware of and willing to use long-acting injectable PrEP when made available. The initiation of HIV long-acting injectable PrEP has the potential to increase protection options among female barmaids who are a population at risk of HIV infection.
Online veröffentlicht: 19. März 2025
Gesehen am 08.10.2025